Synthesis of new 9H-Carbazole derivatives - Alaraji, Suad; Naser, Ahmed; Alsoultany, Nahed (Iraqi Journal of Science, 2024)
The aim of the present work is to synthesis of new 9-ethyl carbazole derivatives .The 3-acetyl-9-ethyl carbazole was achieved by the reaction of compound (1) with acetyl chloride in the presence of aluminum chloride to give compound (2). Reaction of compound (2) with a ppropriate aromatic aldehyde yielded 3-(3-Phenyl -1-Oxy propen-1-yl)9-Ethyl carbazole(3a-3h).The reaction of (3) with hydrazine hydrate gave 3-(5-aryl-4, 5-Dihydro-3-pyrozolyl)9-Ethyl carbazole(4a-4h). Also compound (3) reacted with phenyl hydrazine gave 3-(1-phenyl-5-aryl-4-pyrozoline-3-yl)9-Ethyl carbazole (5a-5h). The reaction of compound (3) with guanidine carbonate in presence of NaOH (40%) gave the 3-(2-amino-6-aryl-4-pyrimidinyl)9-Ethyl carbazole (6a-6h). The prepared compounds were conformed by TLC, FT-IR and some of them 1H-NMR.